THE REPRESENTATION OF LIFESTYLES AND CONSUMPTION CULTURE IN TELEVISION DRAMAS: “GOSSIP GIRL” SERIES* - Tolga Gürocak (International Journal of Eurasia Social Sciences, 2023)
The research examines the lifestyle and consumption phenomena presented through the media and television. Based on the methodological differences in the dystopian novels “1984” and “Brave New World”, it is thought that Huxley’s novel finds more application areas in the contemporary world. In this direction, it was deemed appropriate to examine the media contents, which are the dominant force in the spread of consumer culture and lifestyles and the dominant ideology. The experiences presented in the television series not only enable young people to adapt to the consumer culture but also bring the concept of lifestyle to the fore and make young people a part of the consumption society. The research determined the “Gossip Girl” series as the study universe. Content analysis was used as a data collection technique and a situation determination was tried to be made. Eight categories were determined to examine the lifestyles and consumption activities of the nine main characters. Content analysis was used as a data collection technique, and a situation determination was tried to be made. To examine the lifestyles and consumption activities of the nine main characters in the four episodes of the series included in the study sample, eight different categories were determined. According to the results obtained from the data, the series’ producers present the consumption to the audience in an implicit way with indirect narrations instead of showing the characters while shopping. In this way, possible reactions of the audience are restrained as much as possible. In addition, the research has shown that the phenomenon of lifestyles has ceased to be the privilege of a particular group today and has taken a form that serves to influence the whole society. Consumption and lifestyles have become independent of time and space and have begun to dominate all parts of life. This situation, which was realized thanks to technological developments, was also supported by the content analysis method carried out in the study.